Exploring the Intersection (Menggali Persimpangan): Process Theology and Karl Barth's Theology (Teologi Proses dan Teologi Karl Barth) - Pandiangan, Tumpal (Moriah Theological Seminary, 2024)
This study examines process theology from the perspective of Karl Barth’s theology, aiming to identify the similarities and differences between the two. A literature review was conducted to answer the following key questions: (i) What are the commonalities between Barth’s and Whitehead’s thought? (ii) What are the main differences between Barth’s theology and Whitehead’s theory, despite the existing similarities? (iii) How can process theology and Barth’s theology complement and challenge each other? The findings of this study indicate that: (i) Both theologies can be understood within the framework of God’s Word, (ii) There are significant similarities and differences between Barth and Whitehead’s thoughts, highlighting the points of convergence and divergence in their approaches to transcendence. This research is conducted with humility, grounded in a continuous search for understanding God’s will. Penelitian ini mengkaji teologi proses dari perspektif teologi Karl Barth dengan tujuan untuk menemukan persamaan dan perbedaan antara keduanya. Analisis dilakukan melalui studi pustaka untuk menjawab beberapa pertanyaan utama: (i) Apa saja kesamaan yang dapat ditemukan antara pemikiran Barth dan Whitehead? (ii) Apa perbedaan utama antara teologi Barth dan teori Whitehead, meskipun terdapat kesamaan di beberapa aspek? (iii) Bagaimana teologi proses dan teologi Barth dapat saling melengkapi dan menantang satu sama lain? Temuan dari studi ini menunjukkan bahwa: (i) Kedua teologi dapat dipahami dalam konteks Firman Tuhan, (ii) Terdapat kesamaan dan perbedaan yang signifikan antara pemikiran Barth dan Whitehead, serta titik temu dan perbedaan yang menggarisbawahi pendekatan mereka terhadap transendensi. Penelitian ini dilakukan dengan kerendahan hati, berlandaskan pencarian yang berkelanjutan untuk memahami kehendak Tuhan.